Kebijakan Tata Kelola Kawasan Pembangunan Centre Point of Indonesia di Kota Makassar Sulawesi Selatan - Muhammad Guntur; Muhammad Luthfi Siraj (Syntax Idea)
Makassar City, South Sulawesi, is one of the important cities in Indonesia that has the potential to become the center of economic development, trade, and tourism in eastern Indonesia. In an effort to increase this potential, the Makassar City Government has formulated a policy on the governance of the Center Point of Indonesia development area. The method used in this research is the literature review method with data sources coming from, articles, books, reports, and other research. The results show that collaboration between the government, the private sector, and the community is needed to implement existing policies. The governance policy of the Centre Point of Indonesia (CPI) development area in Makassar City aims to regulate and develop the area in a planned, sustainable manner, and involves various aspects such as spatial planning, environmental management, land use, and good transportation. Collaboration between local government, community, developers, investors, and related experts is the key to success in achieving successful development goals.